Study on Irrigation and Fertigation Scheduling for Sustainable Sugarcane Initiative (SSI) through Subsurface Drip Irrigation - Manikandan, M.; Thiyagarajan, G. (Cutting-edge Research in Agricultural Sciences Vol. 13, 2021)
Sustainable Sugarcane Initiative (SSI) under Sub Surface Drip Irrigation (SSDI) is becoming popular among the farmers because of high output with minimum input. Even though the benefits of SSI under SSDI are understood by farmers, development of optimal irrigation and fertigation schedule is very much necessary. Field trials were carried out at Agricultural Research Station, Bhavanisagar for three years to develop an optimal irrigation and fertigation schedule for SSI for Western Agro climatic zone. The experiment was taken in randomized block design with three replications. The experiment consisted of eight treatments of which six treatments comprised of SSDI with three irrigation regimes of 100, 80 and 60% pan evaporation and two fertigation levels of 100 and 75% of recommended N & K and two treatments in surface drip irrigation (SDI) with 100 % pan evaporation (PE) + 100% RD and 100% PE + 75% RD of N&K through fertigation. The results of this study revealed that SSDI with 60 per cent PE + 100 per cent RD of N&K through fertigation recorded lower water use (1004 mm) and higher WUE (113 kg/ha mm). However, significantly higher and comparable yield of sugarcane (148 t/ha) was recorded in SSDI with 100 % PE + 100 pe cent RD of N&K through fertigation and surface drip irrigation with 100% PE + 100% RD of N&K through fertigation. The net return (Rs. 2,09,405 per ha) and B:C ratio (2.6) were higher in SSDI with 100% PE + 100% RD of N&K through fertigation treatment.